2016
DOI: 10.1186/s40497-016-0045-z
|View full text |Cite
|
Sign up to set email alerts
|

Credit rationing’s determinants of Small and Medium Enterprises (SMEs) in Chittagong, Bangladesh

Abstract: Small and medium enterprises (SMEs) contribute immensely to Gross Domestic Product (GDP) and they have a significant influence in growth of economy. However, SMEs are constrained in their access to formal credit as financial institutions fail to grant credit due to information asymmetry. This study investigates the credit rationing of SMEs in the city of Chittagong. A sample of 200 firms was selected and analyzed using descriptive statistics and multinomial logit regression. The result suggests that 89 % of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 11 publications
2
16
0
7
Order By: Relevance
“…Diversas investigaciones relacionan el tamaño y la edad de la empresa para explicar el racionamiento de crédito que padecen las pymes (Hoque, Sultana, & Thalil, 2016;McCarthy et al, 2013;Freel, Carter, Tagg, & Mason, 2012;Ange-lini, Salvo, & Ferri, 1998). Así, es ampliamente aceptado que las pequeñas empresas afrontan mayores dificultades que las grandes empresas en el mercado de crédito.…”
Section: Tamaño Y Edad De La Empresaunclassified
See 3 more Smart Citations
“…Diversas investigaciones relacionan el tamaño y la edad de la empresa para explicar el racionamiento de crédito que padecen las pymes (Hoque, Sultana, & Thalil, 2016;McCarthy et al, 2013;Freel, Carter, Tagg, & Mason, 2012;Ange-lini, Salvo, & Ferri, 1998). Así, es ampliamente aceptado que las pequeñas empresas afrontan mayores dificultades que las grandes empresas en el mercado de crédito.…”
Section: Tamaño Y Edad De La Empresaunclassified
“…Diversos estudios han tratado de encontrar relaciones entre el racionamiento de crédito a las empresas y la edad, el género y el nivel de instrucción del gerente (Hoque et al, 2016;Freel et al, 2012). En concreto, Hoque et al(2016) hallan que la edad y el sexo del dueño principal de la empresa tienen un impacto significativo sobre el racionamiento de crédito.…”
Section: Capital Humano: Edad Experiencia Nivel De Educación Y Géneunclassified
See 2 more Smart Citations
“…Beck et al (2006) use the World Business Environment Survey (WBES) and fi nd that collateral requirements are the third most important diffi culty in fi nancing for SMEs while high interest rates and lack of long-term loans are the fi rst and second ones. In the context of Bangladesh, Hoque et al (2016) found that 44.5% of their respondents did not apply for bank loans due to being unable to pledge collateral and therefore, they had a fear to get rejection on a loan application. stated that the main reason why banks ask for collateral while lending to SMEs is mainly due to the ex-ante information gap between lenders and borrowers and if the information gap can be shortened it will also reduce the collateral requirement for SMEs .…”
Section: Introductionmentioning
confidence: 99%